PCR Diagnosis of Small Hive Beetles - Ouessou Idrissou, Franck (Insects, 2018)
Small hive beetles (SHBs), Aethina tumida, are parasites of social bee colonies native to sub-Saharan Africa and have become an invasive species at a global scale. Reliable Polymerase Chain Reaction (PCR) diagnosis of this mandatory pest is required to limit its further spread and impact. Here, we have developed SHB primers, which amplify for 10 native African locations and 10 reported introductions, but not for three closely related species (Aethina concolor, Aethina flavicollis, and Aethina inconspicua). We also show that adult honey bee workers can be used as matrices for PCR-based detection of SHBs. The sensitivity of this novel method appears to be 100%, which is identical to conventional visual screenings. Furthermore, the specificity of this novel approach was also high (90.91%). Since both sensitivity and specificity are high, we recommend this novel PCR method and the new primers for routine surveillance of hives in high-risk areas.